Epitaxy of 2D chalcogenides: Aspects and consequences of weak van der Waals coupling. (March 2021) - Mortelmans, Wouter; De Gendt, Stefan; Heyns, Marc; Merckling, Clement
Graphical abstract: Abstract: The application of new materials in nanotechnology opens new perspectives and enables ground-breaking innovations. Two-dimensional van der Waals (vdW) materials and more specific, 2D chalcogenides are a promising class of new materials awaiting their usage in the semiconductor industry applications. However, the integration of 2D chalcogenides relying on industry-compatible manufacturing processes is still a major challenge. This is currently restricting the application of such new materials to the research laboratories environment mainly. The large-area and single-crystalline epitaxial growth of 2D chalcogenides is one of the most important requirements to meet the challenging demands implied by the semiconductor industry. This review contributes to a more generalized understanding on the integration of vdW materials - and more specific 2D chalcogenides - through the growth process of epitaxy. Important epitaxial growth aspects such as in-plane registry, stacking faults and strain formation are reviewed for both vdW and quasi-vdW epitaxy processes of 2D chalcogenides. The control on such growth aspects is more challenging resulting from the weaker (quasi-)vdW epi-layer/epi-substrate coupling. Consequently, nucleation density appears as a key parameter proportional to defect density in large-area 2D chalcogenide epitaxy. Therefore, a systematic review on the nucleation density of transition metal dichalcogenides obtained from essential large-area growth techniques such as molecular beam epitaxy (MBE), metalorganic vapor phase epitaxy (MOVPE) and chemical vapor epitaxy (CVE) is presented. As a result, the proposed insights allow to pursue further the aspiration of large-area, single-crystalline and defect-free epitaxial integration of (quasi-)vdW homo- and heterostructures into the semiconductor industry.